Cryptogein and capsicein promote defence responses in Quercus suber against Phytophthora cinnamomi infection - Medeira, Clara; Quartin, Virgínia; Maia, Isabel; Diniz, Inês; Matos, Mª Céu; Semedo, José Nobre; Scotti-Campos, Paula; Ramalho, José C; Pais, Isabel P; Ramos, Paula; Melo, Elvira; Leitão, António E; et al. (European Journal of Plant Pathology, 2012)
The decline of cork oak (Quercus suber) stands in Iberian Peninsula is associated with infection by Phytophthora cinnamomi. Most Phytophthora species secrete elicitins, which can enhance defence reactions against some pathogens. Here cytological and physiological effects of the elicitins cryptogein and capsicein on cork oak root infection by P. cinnamomi were evaluated. The progression of the pathogen in root tissue and its effects on total fatty acid (TFA) composition of roots and leaves were analysed in seedlings. Net photosynthesis (Pn), stomatal conductance (gs ), chlorophyll a fluorescence measurements (quantum yield of linear electron transport ϕe , photochemical quenching qP, non-photochemical quenching NPQ) and carotenoid determinations were carried out in well established (4 months) plants. In elicitin-treated roots, 2 days after inoculation, the pathogen which presented loss of viability and membrane degradation was mainly restricted to the intercellular spaces of the cortical parenchyma, and did not reach the vascular cylinder. Electron dense materials accumulated in the intercellular spaces of the cortex next to disorganized hyphae, suggested to be related with defence reactions. Cryptogein (or its interaction with P. cinnamomi) induced enhanced lipid synthesis in leaves, which may contribute to preserve membrane stability. P. cinnamomi decreased Pn , gs , ϕe , and qP, whereas elicitintreated plants displayed values similar to controls. Overall, the results indicated a resistance response of cork oak against this oomycete, induced by the elicitins.
Keywords: cytology; decline disease; fluorescence; leaf gas exchanges; Membrane Lipids; photosynthetic pigments

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Comparative field study of spring and summer leaf gas exchange and photobiology of the mediterranean trees Quercus ilex and Phillyrea latifolia - Penuelas, J; Filella, I; Llusia, J; Siscart, D; Piñol, J (Journal of Experimental Botany, 1998)
Summer-induced changes in gas exchange, fluorescence and reflectance were measured on leaves of two co-occurring Mediterranean small trees, Quercus ilex and Phillyrea latifolia, in May, June and July 1996 in Central Catalonia (NE Spain). The humid 1996 summer only produced mild water stress conditions. However, photosynthesis (A) and stomatal conductance (gs) decreased in June and July in both species. In June P. latifolia had higher net photosynthetic rates and lower stomatal conductances than Q. ilex, thus exhibiting higher instantaneous plant water use efficiencies. In agreement with these results, the photo-chemical reflectance index (PRI, calculated as (R570-R531)/(R531+R570)) of P. latifolia was lower, suggesting a possible lower xanthophyll de-epoxidation state. However, P. latifolia had lower ΔF/F′ and therefore a lower electron transport rate (ETR). The behaviour of PRI confirmed previous studies indicating a strong relationship between PRI, ΔF/F′ , and photosynthetic radiation-use efficiency (PRUE). PRI offers a simple, portable means of assessing PRUE with the potential for remote sensing applications. Finally, the possible ecological consequences of these results on the behaviour of the two species studied under the predicted warmer and drier conditions of global change are discussed.
10.1093/jxb/49.319.229
Keywords: fluorescence; intrinsic water use efficiency; net photosynthetic rates; phillyrea latifolia; photochemical efficiency; photochemical reflectance index; photosynthetic radiation-use-efficiency; Quercus ilex; reflectance; Stomatal conductance; summer; water index

Comparative field study of spring and summer leaf gas exchange and photobiology of the mediterranean trees Quercus ilex and Phillyrea latifolia - Penuelas, J.; Filella, I.; Llusia, J.; Siscart, D.; Piñol, J. (Journal of Experimental Botany, 1998)
Summer-induced changes in gas exchange, fluorescence and reflectance were measured on leaves of two co-occurring Mediterranean small trees, Quercus ilex and Phillyrea latifolia, in May, June and July 1996 in Central Catalonia (NE Spain). The humid 1996 summer only produced mild water stress conditions. However, photosynthesis (A) and stomatal conductance (gs) decreased in June and July in both species. In June P. latifolia had higher net photosynthetic rates and lower stomatal conductances than Q. ilex, thus exhibiting higher instantaneous plant water use efficiencies. In agreement with these results, the photo-chemical reflectance index (PRI, calculated as (R570-R531)/(R531+R570)) of P. latifolia was lower, suggesting a possible lower xanthophyll de-epoxidation state. However, P. latifolia had lower ΔF/F′ and therefore a lower electron transport rate (ETR). The behaviour of PRI confirmed previous studies indicating a strong relationship between PRI, ΔF/F′ , and photosynthetic radiation-use efficiency (PRUE). PRI offers a simple, portable means of assessing PRUE with the potential for remote sensing applications. Finally, the possible ecological consequences of these results on the behaviour of the two species studied under the predicted warmer and drier conditions of global change are discussed.
10.1093/jxb/49.319.22910.1093/jxb/49.319.229
Keywords: fluorescence; intrinsic water use efficiency; net photosynthetic rates; phillyrea latifolia; photochemical efficiency; photochemical reflectance index; photosynthetic radiation-use-efficiency; Quercus ilex; reflectance; Stomatal conductance; summer; water index

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - Faria, T; Cerasoli, S; Garcia-Plazaola, J I; Guimaraes, M P; Abadía, A; Raschi, A; Miglietta, F; Pereira, J S; Chaves, M M (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Ecophysiological studies of Mediterranean plant species at the Castelporziano estate - Manes, Fausto; Seufert, Günther; Vitale, Marcello (Atmospheric Environment, 1997)
e aim of this work was to characterize the eco-physiological performance of the main plant species of the Castelporziano site by single leaf investigations. We measured the leaf gas exchange of Quercus ilex L., Pinus pinea L., Pistacia lentiscus L. and Asphodelus microcarpus L. for several days. Additionally, the xylem water potential of Quercus ibex, Pinus pinea and Pistacia lentiscus was recorded in order to obtain more physiological background information for the discussion of the trace gas emissions. This study indicates significantly different physiological responses to the different environmental condi- tions. In particular, summer conditions (high values of light, air temperature and low xylem water potentials) caused the depression of photosynthesis in Quercus ibex and Pinus pinea but did not affect photosynthesis of Pistacia lentiscus and Asphodelus microcarpus. This should be taken into account when discussing VOC emission rates and fluxes
Keywords: fluorescence; Phenology; photosynthesis; Transpiration; VOCs; Xylem water potential

Drought and photosystem II activity in two Mediterranean oaks - Méthy, M; Damesin, C; Rambal, S (Ann. For. Sci., 1996)
The responses of photosystem II (PS II) to drought were analysed on two Mediterranean oak species, Quercus ilex and Q pubescens, using the chlorophyll fluorescence pulse-amplitude-modulation technique. The maximal PS II photochemical efficiency (Fv/Fm) of the evergreen Q ilex and the deciduous Q pubescens oaks was only affected when leaf predawn water potential was lower than -4 MPa. This value is rarely observed on mature trees growing in the field, but can be undergone by young seedlings during drought periods, hence confirming the stability of PS II. Whatever the irradiance, drought resulted, in both species, in lower values of PS II photochemical efficiency in a light-adapted state (ΔF/F m'), due to stomatal closure and/or a direct inhibition of the dark reactions of photosynthesis. Diurnal decreases of Fv/Fm of 30 min dark-adapted leaves were greater for lower predawn water potential; a recovery was observed in the late afternoon. The reversible decreases in the diurnal time-courses of maximal fluorescence led us to assume the onset of protective mechanisms from permanent photodamages in Q ilex and, to a lesser extent, in Q pubescens.
Keywords: fluorescence; photoinhibition; Photosystem II; Quercus; water stress

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M. M.; Pereira, J. S.; Cerasoli, S.; CliftonBrown, J.; Miglietta, F.; Raschi, A.; Chaves J. S. ;Cerasoli, S. ;Clifton Brown (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)The following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD label: Fisiologia - CO2 elevado
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A; Chaves J. S.;Cerasoli,S.;Clifton Brown,J.;Miglietta,F.;Raschi,A., M M ;Pereira (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits

Effets de températures sub-létales sur l'appareil photosynthétique du chêne vert (Quercus ilex L) - Trabaud, L; Méthy, M (Ann. For. Sci., 1992)
Effects of sub-lethal temperatures on the photosynthetic apparatus of Quercus ilex L. Resistance to high temperatures by the photosynthetic system of leaves of a sclerophyllous tree growing in the Mediterranean basin (Quercus ilex) has been studied using the fluorescence induction technique. Registration of the kinetics with determination of fluorescence decrease ratio was carried out every month for 1 year. According to the dates of sampling, leaves were sorted into 2 categories: > 3 months and < 3 months. They were heated at temperatures of 50, 55 and 60 °C for periods ranging from 0 to 30 min. After sclerification was established (≈ 1 month old) leaves withstood heat with only limited damage at 50 °C. In contrast, the photosynthetic system was totally destroyed when exposed to 60 °C for 30 min. Leaves collected in July displayed some adaptation to high temperatures. The consequences on the functioning of Q ilex in an environment with high temperatures have been examined.
Keywords: fluorescence; photosynthesis; Quercus ilex; thermal stress

Fluorescence Parameters Measured Concurrently with Net Photosynthesis to Investigate Chloroplastic CO2 Concentration in Leaves of Quercus ilex L. - Di Marco, Giorgio; Manes, Fausto; Tricoli, Domenico; Vitale, Elisabetta (Journal of Plant Physiology, 1990)
Summary The relationship between net carbon assimilation and non-photochemical quenching (qN) was studied in Q. ilex. In leaf discs, in saturating C02 at various irradiances, qN responded linearly in a 1:1 relationship to 1-A/Ap, which represents the proportion of light energy that is not used in photosynthesis. In calculating Ap, a measured, maximal quantum yield for CO2 fixation of 0.080 for 1-year-oldleaves and 0.085 for young leaveswas used. In attached leaves, under natural conditions, this 1: 1 relation was found when a quantum yield of 0.020 and 0.031 was adopted respectively. According to a model of leaf photosynthesis these quantum yields correspond to stromal CO2 concentrations of 90 and 120μLL L-1, in contrast to an average value of substomatal CO2 concentration of 280μLL L-1 found through gas exchange measurements. Similar results were obtained when the relative increase of fluorescence, observed after a saturating flash given during steady photosynthesis at different irradiances, was plotted against the quantum yield of CO2 fixation. The slope of this relation in attached leaves differed from the slope obtained in saturating CO2 in the leaf discs to such an extent as to indicate stromal CO2 concentrations slightly lower compared with the above values obtained by using qE. The marked difference between stromal and substomatal CO2 concentration could be explained by the highly sclerophyllous character of Q. ilex leaves.
Keywords: carbon assimilation; fluorescence; fluorescence quenching; quantum yield; Quercus ilex; stromal CO2